KEBUDAYAAN MASYARAKAT KAMPUNG NAGA KABUPATEN TASIKMALAYA - Nia Nursalis; Maulina Sofwan; Reka Mustika; Aini Loita; Ali Nurdin (Magelaran: Jurnal Pendidikan Seni, 2019)
This article describes the results of a qualitative descriptive study of the culture of Kampung Naga community. Kampung Naga is a traditional village located in Neglasari Village, Salawu District, Tasikmalaya Regency, West Java. The people still hold strong the traditions inherited from their ancestors where they live in an order that is encompassed by an atmosphere of modesty and a sticky environment of traditional wisdom. Kampung Naga's community culture is very diverse starting from the equipment system and all the activities they do all depend on nature and are still very traditional. Most people work as farmers. There are two government institutions in Naga village, namely formal institutions and traditional institutions. The Kampung Naga community has a variety of arts to traditional ceremonies. Among other things, art is scattered, angklung bareung, beluk, and rengkong. There are three arts pairs in Kampung Naga including Terebang Gembrung, Terebang Sejat and Angklung Bareung. While traditional ceremonies are often carried out, namely the solitary ceremony, the purpose of gratitude and traditional marriage. Although the community still adheres to the ancestral traditions of their ancestral knowledge system, they are not left behind. Although almost all people embrace Islam, but in living ancestral customs, the people of Kampung Naga are very obedient and steadfast in carrying out every customary ritual that is considered taboo if not done. They assume that if they do not undergo traditional rituals inherited from their ancestors, it is feared that they will bring harm.